2016
DOI: 10.22158/wjer.v3n2p267
|View full text |Cite
|
Sign up to set email alerts
|

Design and Validation of a Questionnaire to Analyze University Dropout—CADES

Abstract: Educational institutions and, in particular, universities must establish a clear vision and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 24 publications
0
21
0
3
Order By: Relevance
“…In the same line of argument, Kori et al (2015) in their research suggested the following factors' categorization: demographic, student income, academic performance, learning motivation, social integration and institutional characteristics (Kori et al, 2015). Similarly, Díaz & De León (2016) and Alban & Mauricio (2019) propose their factorial categorization. Accordingly, the above could be combined as follows:…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In the same line of argument, Kori et al (2015) in their research suggested the following factors' categorization: demographic, student income, academic performance, learning motivation, social integration and institutional characteristics (Kori et al, 2015). Similarly, Díaz & De León (2016) and Alban & Mauricio (2019) propose their factorial categorization. Accordingly, the above could be combined as follows:…”
Section: Introductionmentioning
confidence: 94%
“…Nevertheless, the definition of student dropout remains under consideration; different sets of factors and phenomena (Díaz & De León, 2016) along with the evolution of various approaches such as the educational, individual and the holistic one integrating the above (Bardach et al, 2019) could not either be neglected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some useful outputs in this regard are found in Díaz and De León (2016) for measuring dropout intentions, an indicator of student retention (SR), Maddox and Nicholson (2014) on student satisfaction and Soldner, Smither, Parsons and Peek (2016) for measuring student persistence, a proxy for SR. To attain a fuller understanding of how students value the HEIs in which they study, an instrument that can capture multiple dimensions of IE and that is developed and tested in the local context, is required. Although this article cannot claim to fill this gap, it strives to make a contribution in that regard.…”
Section: Purpose Of the Study And Research Objectivesmentioning
confidence: 99%
“…Inspired by Volkwein's (2011) vital observation regarding the primacy of student learning outcomes in defining IE, a search of the relevant literature for what might constitute such outcomes revealed four key themes. This review privileges a sociological perspective (Díaz & De León, 2016), focusing on the institutional determinants of each outcome as they are more likely to signify IE and therefore highlight critical areas for intervention (Hilton & Gray, 2017), as opposed to other confounding or mediating factors. Student educational outcomes (SEOs) are used in this study to represent a set of four distinct but related outcomes, which have been reported by other scholars to various degrees.…”
Section: Student Educational Outcomesmentioning
confidence: 99%